UTILIZATION OF FAMILY MEDICINE PLANTS FOR TREATMENT OF FAMILIES IN KEBUN BUNGA VILLAGE OF SUKARAMI DISTRICT, PALEMBANG - Aseptianova, Aseptianova (Institut Seni Indonesia Padangpanjang, 2019)
Along with the development of knowledge and technology, traditional medicines has been proven to be useful in a laboratory test and guaranteed safe for consumption and can cure diseases without causing side effects. Efforts by the community are also recommended by the government in improving health status, one of which is the utilization of Family Medicinal Plants. We can use community service as part of an independent health promotion effort for the community. The purpose of this community service is that the community knows the benefits of plants as medicinal plants so that the community can cultivate and preserve various medicinal plants so that they can reduce medical costs. This community service uses a participatory model. The results of this community service show that the community has begun to use and cultivate Family Medicinal Plants (TOGA) as well as productive plants. In the Sukarami sub-district, vacant land has been used for various plants ranging from ginger, turmeric, kencur, durian, guava, soursop, longan, rambutan, and jackfruit. The purpose of this community service is that the community knows the benefits of plants as medicinal plants so that the community can cultivate and preserve various medicinal plants to reduce medical costs. This community service uses a participatory model. The results of this community service show that the community has begun to use and cultivate Family Medicinal Plants (TOGA) as well as productive plants. In the Sukarami sub-district, vacant land has been used for various plants ranging from ginger, turmeric, kencur, durian, guava, soursop, longan, rambutan, and jackfruit.